2013
DOI: 10.1002/ps.3661
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterisation of an HD1‐like Bacillus thuringiensis isolate with a high insecticidal activity against Spodoptera littoralis (Lepidoptera: Noctuidae)

Abstract: On the basis of its potent insecticidal activity and its high level of δ-endotoxin production, the BUPM28 isolate can be considered to be an effective alternative for the control of S. littoralis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…The insecticidal activity of spore/crystal mixtures is an effective way to search for native Bt isolates having new entomocidal properties [ 7 , 32 , 34 , 35 , 36 ]. In our study, preliminary assays indicated that some of the 18 selected isolates in the collection had high toxicity against Lepidoptera.…”
Section: Discussionmentioning
confidence: 99%
“…The insecticidal activity of spore/crystal mixtures is an effective way to search for native Bt isolates having new entomocidal properties [ 7 , 32 , 34 , 35 , 36 ]. In our study, preliminary assays indicated that some of the 18 selected isolates in the collection had high toxicity against Lepidoptera.…”
Section: Discussionmentioning
confidence: 99%
“…The Egyptian cotton leafworm, Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae) is a native pest to Africa (Shonouda and Osman, 2000;El-Khawas and Abd El-Gawad, 2002), and distributed in many European countries (Pineda et al, 2007;EPPO, 2019), Asia Minor and the Middle East countries (El-Aswad, 2007;El-Sabrout, 2013;Azzouz et al, 2014). Economically, it is a dangerous pest of many field crops and vegetables in North Africa, Middle East countries including Egypt (Kandil et al, 2003) and glasshouses plants and flowers production in Southern Europe (Roques et al, 2008;Abdel-Mageed et al, 2018), as well as various cash and traditional food crops in Africa (Capinera, 2008;Khedr et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although Egyptian cotton leafworm Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae) is a native pest to Africa (Shonouda and Osman, 2000;El-Khawas and Abd El-Gawad, 2002), it is distributed in many European countries (Pineda et al, 2007;Lanzoni et al, 2012;EPPO, 2019), Asia Minor and the Middle East countries (El-Aswad, 2007;El-Sabrout, 2013;Azzouz et al, 2014). S. littoralis caterpillars feed on more than 90 plant species of economic importance belonging to 44 plant families (Kandil et al, 2003;, such as vegetables, horticultural crops and ornamental plants (Dahi, 2005;Amin, 2007;Ismail, 2014;Sut et al, 2017).…”
Section: Introductionmentioning
confidence: 99%